Manajemen Laba dalam Initial Public Offerings dan Faktor yang Mempengaruhinya pada Perusahaan Tercatat di Bursa Efek Jakarta - Irawan, Ronny (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
This research examines the existence of earnings management of the initial public offerings companies at Jakarta Stock Exchange for periods 2000-2005. Test were conducted on 52 selected firms that went public at Jakarta Stock Exchange for the periods 2000-2005. First, the method used to examine earnings management that is modified Jones models in Dechow et al (1995). Second, the method used to know the factors that affecting earnings management. Examined factor is the quality of auditor, shares that retained by owners, financial leverage, the size of the company, assets growth, and sales growth.